Deep-UV-enhanced supercontinuum generated in a tapered gas-filled photonic crystal fiber - Suresh, Mallika Irene; Hammer, Jonas; Joly, Nicolas; Russell, Philip St. John; Tani, Francesco (Optics Letters, 2021)
We present the use of a linearly down-tapered gas-filled hollow-core photonic crystal fiber in a single stage, pumped with pulses froma compact infrared (IR) laser source, to generate a supercontinuum (SC) carrying significant spectral power in the deep ultraviolet (UV) [200-300 nm]. The generated SC extends from the near IR down to 213 nm with 0.58 mW/nm and down to 220 nm with 0.83 mW/nm in the deepUV.
CRIS-Team Scopus Importer:2021-09-17